2011
DOI: 10.1177/0148558x11401218
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Earnings Management in the Pre– and Post–Sarbanes-Oxley Act Regimes

Abstract: Backdating stock options, a practice that retroactively adjusts stock option grant dates to lower the exercise price, has raised governance, legal, accounting, tax, and auditing concerns. The practice of backdating options generally is believed to be a result of both ineffective corporate governance and management opportunism. Both of these factors have been linked to a higher level of discretionary accruals adjustments. This study examines the accruals-based earnings management patterns for a group of firms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
35
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 40 publications
7
35
1
1
Order By: Relevance
“…Even though the relationship is negative, RELAUCOM is insignificant for classification shifting. This finding is consistent with prior studies (Zalata and Roberts, 2015;Hossain et al 2011) and indicates that effective corporate governance mechanism in an organisation has negative impact on earnings management practices. Notwithstanding, the results show that religiosity of the firms' environment has the potential to shape the attitudes and behaviour of firms' managers even when there is a good corporate governance mechanism in operation.…”
Section: Religiosity and Corporate Governancesupporting
confidence: 92%
See 1 more Smart Citation
“…Even though the relationship is negative, RELAUCOM is insignificant for classification shifting. This finding is consistent with prior studies (Zalata and Roberts, 2015;Hossain et al 2011) and indicates that effective corporate governance mechanism in an organisation has negative impact on earnings management practices. Notwithstanding, the results show that religiosity of the firms' environment has the potential to shape the attitudes and behaviour of firms' managers even when there is a good corporate governance mechanism in operation.…”
Section: Religiosity and Corporate Governancesupporting
confidence: 92%
“…For example, (Xie, Davidson and DaDalt, 2003;Peasnell, Pope and Young, 2005) observe a negative association between board tenure, proportion of independent directors and accrual-based earnings management. Again, (Hossain, Mitra, Rezaee and Sarath, 2011) observe that the relationship between board size, number of meetings and accrual-based earnings management is negative. Also, audit committees (Abbott, Parker, Peters and Raghunandan, 2003), number of meetings and financial expertise (Coles, Daniel and Naveen, 2008), CEO tenure (Cadman and Sunder, 2014), number of outside directors (Chau and Gray, 2010) and CEO reputation (Francis, Huang, Rajgopal and Zang, 2008) have been found to affect earning management.…”
Section: Introductionmentioning
confidence: 92%
“…The Cadbury Report (1992) suggested three or four meetings a year, whereas the combined code recommended that boards should meet regularly to discharge their duties efficiently. Supporting this, Hossain et al (2011) and Xie et al (2003) found that accrual-based earnings management is negatively related to board and audit committee meeting frequency, whereas Abbott et al (2004) similarly found that the probability of restatements is lower in firms with more audit committee meetings. Therefore, the number of meetings is also included.…”
mentioning
confidence: 87%
“…The empirical findings support the importance of financial experience. For example, Xie et al (2003) found that a higher proportion of audit committee members with a corporate or investment banking background is related to lower accruals management, whereas Bedard et al (2004), Hossain et al (2011), and Yang and Krishnan (2005) found that the existence of at least one financial expert in the audit committee lead to lower accrual management. Similarly, the probability of restatement is lower when an audit committee has at least one member with financial experience (Abbott et al, 2004).…”
mentioning
confidence: 99%
“…lucros do ano subsequente. (Hossain et al, 2011) O tipo de explicação afeta significativamente a associação entre as explicações de desempenho e o gerenciamento de resultado, e esse efeito torna-se mais pronunciado em um regime institucional obrigatório onde os custos obrigatórios e os litígios esperados são maiores.…”
Section: Conclusãounclassified